Pengaruh Model Pembelajaran Blended Learning Terhadap Hasil Belajar Fisika - Pertiwi,; Akhfar, Mariani; Taqwin, Muhammad; Ena, Hermina; Hajeriati,; Fatmawati, Titin (Al-Khazini: Jurnal Pendidikan Fisika, 2022)
This research is an experimental study using a posttest only control design. The research population was all the students of class XI MIA SMA Negeri 1 Satarmese with totaly 78 students from 3 classes. Simple random sampling was used to determine the control class was XI MIA 1 and the experimental class was XI MIA 2. The instruments used were tests, observations and documentation. The data obtained were analyzed by descriptive statistics and independent sample t-test different tests to answer the research problem formulation in the form of: (1) how much students' physics learning outcomes without applying the blended learning model in class XI MIA SMA Negeri 1 Satarmese. (2) how much the physics learning outcomes of students who apply the blended learning model in class XI MIA SMA Negeri 1 Satarmese. (3) is there a significant effect of the blended learning model on the physics learning outcomes of students in class XI MIA SMA Negeri 1 Satarmese. The research was conducted on Dynamic Fluids so that the results showed that Blended learning model was categorized as adequate. This can be seen from the average student learning outcomes in the experimental class greater than the average student learning outcome in the control class. And the results of hypothesis testing using the independent sample t-test with value t-count greater than t-table